Cercariform cells: Another cytologic feature distinguishing solid pseudopapillary neoplasms from pancreatic endocrine neoplasms and acinar cell carcinomas in endoscopic ultrasound‐guided fine‐needle aspirates1. Issue 6 (5th December 2012) - Samad, Arbaz; Shah, Akeesha A.; Stelow, Edward B.; Alsharif, Mariam; Cameron, Stuart E. H.; Pambuccian, Stefan E.
<x xml:space="preserve">Abstract</x> BACKGROUND Solid pseudopapillary neoplasm (SPPN) is a rare tumor of unknown origin that occurs predominantly in the body or tail of the pancreas in young women. The authors recently identified cercariform (Greek: tailed) cells, similar to those described in urothelial carcinomas, as a consistent cytologic feature in ultrasound‐guided fine‐needle aspiration (EUS‐FNA) samples from SPPNs. The objective of the current multi‐institutional study was to define the value of these cells in the differential diagnosis of SPPN with other neoplasms characterized cytologically by the presence of monotonous, uniform cells in pancreatic aspirates: pancreatic neuroendocrine tumors (Pan‐NETs) and acinar cell carcinomas (ACCs). METHODS The files of 4 academic hospitals were searched for SPPNs, Pan‐NETs, and ACCs that were diagnosed by EUS‐FNA. The slides were reviewed, and several cytologic features were recorded semiquantitatively to identify discriminating features between SPPNs, Pan‐NETs, and ACCs. RESULTS From the analysis of 18 SPPNs, 4 ACCs, and 20 Pan‐NETs, the following cytologic features were identified as common to all 3 neoplasms: single cells and rosettes/acinar cell groups, round‐to‐plasmacytoid cells, pale‐to‐granular cytoplasm, fine vacuoles, and binucleated cells. Papillary structures, cercariform cells, large cytoplasmic vacuoles, reniform nuclei, hyaline globules/magenta‐colored material, and degenerative features (cholesterol crystals, calcifications, foam cells, or giant cells) were significantly more common in SPPNs. Prominent nuclear grooves were encountered in only 4 of 18 SPPNs. CONCLUSIONS The current results indicated that the presence of cercariform cells is another useful clue for the cytologic diagnosis of SPPN in challenging cases. Cancer (Cancer Cytopathol) 2013;121:298–310. © 2012 American Cancer Society.